Benefits of Escin for Decompression Sickness in Bama Pigs by Endothelial-Targeting Protection - Qing, Long; Meng, Wentao; Zhang, Wei; Yi, Hong-jie; Zhang, Kun; Ariyadewa, Dinesh K.; Xu, Wei-gang (Frontiers in Physiology, 2019)
Endothelial dysfunction is involved in the pathogenesis of decompression sickness (DCS) and contributes substantively to subsequent inflammatory responses. Escin is well known for its endothelial protection and anti-inflammatory properties, and its protection for DCS has been proved in a rat model. This study aimed to further investigate the protection of escin against DCS in swine. Sixteen swine were subjected to a two-stage experiment with an interval of 7 days. In each stage, seven days before a simulated air dive, the swine were treated with escin or saline. The first group received a successive administration of escin for 7 d prior to the first dive and saline for 7 d prior to the second; the second group was treated with saline and then escin. After decompression, signs of DCS and circulating bubbles were monitored, and blood was sampled for platelet count and determination of inflammatory and endothelia related indices. The death rate of DCS was markedly decreased in swine treated with escin compared with that in animals treated with saline, though not statistically significant due to the limited number of animals. Escin had no effect on bubble load but significantly ameliorated platelet reduction and endothelial dysfunction, as well as oxidative and inflammatory responses. The results further suggest the beneficial effects of escin on DCS by its endothelia-protective properties and escin has the potential to be a candidate drug for DCS prevention and treatment.